Hydrogen sulphide ameliorating skeletal muscle atrophy in db/db mice via Muscle RING finger 1 S‐sulfhydration. Issue 16 (7th July 2020) - Lu, Fangping; Lu, Baoling; Zhang, Linxue; Wen, JingChen; Wang, Mengyi; Zhang, Shiwu; Li, Qianzhu; Shu, Feng; Sun, Yu; Liu, Ning; Peng, Shuo; Zhao, Yajun; et al.
Abstract: Muscle atrophy occurs in many pathological states, including cancer, diabetes and sepsis, whose results primarily from accelerated protein degradation and activation of the ubiquitin‐proteasome pathway. Expression of Muscle RING finger 1 (MuRF1), an E3 ubiquitin ligase, was increased to induce the loss of muscle mass in diabetic condition. However, hydrogen sulphide (H2 S) plays a crucial role in the variety of physiological functions, including antihypertension, antiproliferation and antioxidant. In this study, db/db mice and C2C12 myoblasts treated by high glucose and palmitate and oleate were chose as animal and cellular models. We explored how exogenous H2 S attenuated the degradation of skeletal muscle via the modification of MuRF1 S‐sulfhydration in db/db mice. Our results show cystathionine‐r‐lyase expression, and H2 S level in skeletal muscle of db/db mice was reduced. Simultaneously, exogenous H2 S could alleviate ROS production and reverse expression of ER stress protein markers. Exogenous H2 S could decrease the ubiquitination level of MYOM1 and MYH4 in db/db mice. In addition, exogenous H2 S reduced the interaction between MuRF1 with MYOM1 and MYH4 via MuRF1 S‐sulfhydration. Based on these results, we establish that H2 S prevented the degradation of skeletal muscle via MuRF1 S‐sulfhydration at the site of Cys44 in db/db mice.